Abuse of confidence as criminal act - Анісімов, Г. М. (Problems of legality, 2015)
The article studies objective and subjective evidence of abuse of confidence as criminal act, which serves as the base for defining of its generic term; subordinate concept of crimes committed through abuse of confidence, delimiting of adjacent crimes;relation between fraud and abuse of confidence as independent criminal acts.